Driving Management Change: Green Transformational Leadership as a Catalyst for Sustainable Management A Systematic Literature Review - Siti Rafika Arman; Andriyanti Asianto; Abdul Haeba Ramli; Lia Amalia; Ferryal Abadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Research on green transformational leadership has attracted academic attention in recent years. However, a comprehensive analysis of the development of green transformational leadership and its role in changes that occur within organizations has not been conducted. To address this gap, this literature aims to review the development of green transformational leadership and analyze the role of green transformational leadership in changes that occur at both the individual and organizational levels. A systematic literature review approach was used in writing this article. Selected journal articles are analyzed to determine their relationship and relevance to the topic of Green Transformational Leadership. Research on Green Transformational Leadership has increased over the past 12 years. In total, 25 articles were examined in this literature review, a large portion of literature used quantitative approaches and were mostly studied in the Asian continent. Based on the findings analyzed, Transformational leadership styles have shifted towards a sustainable approach because of the emphasized responsibility for environmentally friendly behavioral practices for organizations. In addition, Green Transformational Leadership plays an important role in management change at both the individual and organizational levels. This study describes the structural overview of 25 journal articles published from 2013 to early 2025. This review presents an in-depth discussion of the current state of research, trends and future research directions on green transformational leadership. Keywords: Green Transformational Leadership; Change Management; Sustainable Management